2016
DOI: 10.3389/fvets.2016.00005
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Perceptions of Animal Contact and Associated Health Outcomes in Pregnant Women and New Mothers

Abstract: Companion animals play an important role in our society. However, pregnant women and new mothers might have specific concerns about animal-associated health outcomes because of their altered immune function and posture as well as their newborn babies. The study was conducted to collect baseline data for developing an evidence-based intervention for pregnant women and new mothers to help them adopt certain behaviors to prevent adverse animal-associated health outcomes. A survey, using the Health Belief Model as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, in both cases, the role of veterinarians as educators was neglected. In fact, there are several studies reporting the lack of transmission of information about zoonotic diseases and their potential hazards by veterinarians to animal owners [ 20 , 33 , 45 , 75 , 76 , 77 ]. Pet owners indicated that veterinarians only discuss this issue when asked or whenever zoonoses had been diagnosed in pets [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in both cases, the role of veterinarians as educators was neglected. In fact, there are several studies reporting the lack of transmission of information about zoonotic diseases and their potential hazards by veterinarians to animal owners [ 20 , 33 , 45 , 75 , 76 , 77 ]. Pet owners indicated that veterinarians only discuss this issue when asked or whenever zoonoses had been diagnosed in pets [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study are consistent with those of others regarding the role of physicians in transmitting information about zoonoses. In fact, the limited involvement of physicians in questioning the detention of pets by their patients, advising on protective measures and discussing potential zoonotic diseases has been described [ 20 , 28 , 45 , 77 , 79 , 80 , 81 ]. This is problematic since animal contact frequently occurs in both pet and non-pet owning households, so individuals without pets but with animal contact will likely not consult a veterinarian.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both cases, the role of veterinarians as educators was neglected. In fact, there are several studies reporting the lack of transmission of information about zoonotic diseases and their potential hazards by veterinarians to animal owners [16,26,28,[64][65][66]. Pet owners indicated that veterinarians only discuss this issue when asked or whenever zoonoses had been diagnosed in pets [65].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study are consistent with those of others regarding the role of physicians in transmitting information about zoonoses. In fact, the limited involvement of physicians in asking about the detention of pets by their patients, advising on protective measures and discussing potential zoonotic diseases has been described [16,24,28,66,[69][70][71]. This is problematic since animal contact frequently occurred in both pet and non-pet owning households, so individuals without pets but with animal contact will likely not consult a veterinarian.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies did not measure the perceptions using the health belief model as in our study, they also found that when interviewing clients with animal contact, the healthcare providers would request information concerning zoonotic transmission and prevention methods. 26,[30][31][32] The importance of cues to action recognized among healthcare providers was supported by previous studies which reported that healthcare providers felt a limitation of disease identification and diagnosis in rural areas with prevalent human-livestock interaction and less confidence to give health advice. 15,33,34 This study was the first, to our knowledge, to examine a potential linkage between animals and human health using the magnitude of households with goats related to women's adverse pregnancy outcomes.…”
Section: Perceptions and Intention To Do Risk Screeningmentioning
confidence: 93%